Um Stomatal conductance and transpiration in Allium sativum L. under water deficiency (Colloquium Agrariae. ISSN: 1809-8215, 2022)
The study aimed to verify the water stress indicators of garlic (Allium sativum L.) submitted to water deficit levels, simulating the effects of possible climatic changes. Considering that A. sativum is a crop known worldwide for its medicinal, culinary properties and applications in the ecological management of agricultural pests and, knowing that the planet is undergoing constant climatic changes, this study becomes essential to understand the influence of these changes on this species cultivation. The treatments were established with water conditions of 100, 75, 50, and 25% of the pot capacity (PC). According to the pot capacity, three bulbils were planted per pot (5 L) containing Plantmax® substrate, irrigated every two days. During the first and last week of the greenhouse treatments, the chlorophyll index was evaluated using a porometer with a seven-day interval between the analysis. The first analysis was performed in the first week of water stress and the last one in the last days of stress. Garlic plants showed sensitivity to water deficit, resulting in less conductance and transpiration in treatments 50% and 75% of water deficit, still without causing production changes. Given this study results, it is concluded